The impact of obesity on female infertility - summary of current knowledge - Izabela Jastrzębska; Oliwia Sysło; Weronika Goliat; Konrad Haraziński; Nikola Rubik; Maksym Gmur; Michał Gajewski; Barbara Sławińska; Zuzanna Błecha; Nicole Tacka (Quality in Sport)
Introduction and Purpose: